Employee Performance Reform Based on Integrity, Organizational Support and Team Work - Sulaiman, Sai (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
The many irregularities in work behavior and the unprofessional civil servants have become the trigger for performance reform in government agencies. This is because the public is furious about the behavior of government employees who are considered arrogant and like to take bribes. Finally, in this digital era, many people publish the poor performance of civil servants on social media, thereby forcing the authorities to reform the performance of their employees. This research was conducted as an effort to look at improving the quality of performance of civil servants based on the values ​​of integrity, organizational support and work teams. To test this objective, a data-based quantitative approach is used. As many as 100 employees of the East Nusa Tenggara provincial religious court were questioned as correspondents. In disclosing this information, an analytical method based on structural equations is used. The results of the study reveal that changing old work patterns is not easy, but efforts to improve and improve must be made, one of which is by instilling the values ​​of integrity, providing large compensation and building a productive work environment. Statistically, there is a trend of improving the quality of employee work when integrity values ​​are implemented in carrying out tasks. In addition, a large compensation system can raise morale, resulting in pleasant and friendly work behavior. Meanwhile, a healthy work environment can affect the psychology of employees to be able to provide the best for their co-workers.